ANALISIS DAMPAK PERKEMBANGAN PARIWISATA KAWASAN PUNCAK 2000 TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT DESA KACINAMBUN KECAMATAN TIGAPANAH KABUPATEN KARO (Jurnal Spasial, 2023)
This study aims to analyze the socio-economic conditions of the people of Kacinambun Village before and after the development of tourism in the Puncak 2000 area and to analyze the impact of the development of tourism in the Puncak 2000 area on the socio-economic conditions of the people of Kacinambun Village, Tigapanah District, Karo Regency. This research was conducted in Kacinambun Village, using purposive sampling with a total sample of 46 people who do business around Kacinambun Village and Puncak 2000 as the people of Kacinambun Village. Data collection techniques in this study are interview and documentation techniques. The data analysis technique used descriptive qualitative analysis. The results of this study indicate that the development of Puncak 2000 tourism has an impact on the socio-economic conditions of the people of Kacinambun Village. The social and economic conditions of the Village community are also getting better after the development of tourism in the 2000 Peak Region. The community experienced social and economic changes after the development of 2000 Peak Area tourism in terms of increasing social activities in the community and increasing economic income and improving village infrastructure. from access roads, networks, places of worship and others. So based on the data obtained, it can be concluded that the development of tourism in the Puncak 2000 area has a positive impact on the people of Kacinambun Village, especially in the social and economic community.